Studies on Analgesic and Anti-Inflammatory Activities of Aerial Parts of Tephrosia Bracteolata GUILL. and PERR. (Fabaceae) in Rodents (Nigerian Journal of Pharmaceutical Research, 2021)
Background:Tephrosia bracteolata is a widespread shrub belonging to the family (Fabaceae) and genus Tephrosia. It is traditionally used for treating rheumatic pains, dropsy and stomach ache.Objectives:In view of the ethnomedicinal claim and the continuous search for new medicinal agents, the phytochemical constituents, analgesic and anti-inflammatory activities of chloroform fraction (CF) of the methanol extract of Tephrosia bracteolata in mice and rats was evaluated.Methods:Preliminary phytochemical screening was conducted using standard method. Analgesic activity of CF (100, 200 and 400 mg/kg body weight orally) was investigated using acetic acid-induced writhing test and thermally induced pain model in mice. Additionally, anti-inflammatory activity was tested by carragenaan-induced paw edema in rats.Results:Phytochemical screening revealed the presence of alkaloids, triterpenes and flavonoids. The oral LD50 of CF was above 2000 mg/kg body weight. CF significantly (p